ANALISIS KEBIJAKAN HUKUM DALAM PENANGANAN KDRT OLEH MILITER: PERBANDINGAN PERADILAN MILITER DAN UMUM: Indonesia - Idris, Idris. (El-Ahli : Jurnal Hukum Keluarga Islam, 2024)
The handling of Domestic Violence (DV) cases involving military personnel often presents a jurisdictional dilemma between military courts and civilian courts. This study aims to analyze legal policies in addressing DV committed by military personnel and to compare the differences in handling such cases between the two judicial systems. The method used is normative juridical with a comparative law approach, including an analysis of military court rulings and civilian court decisions. The research findings reveal significant differences in judicial processes and sentencing. Military courts tend to provide special treatment to perpetrators, taking into account their status as part of the military institution. On the other hand, civilian courts are more focused on the protection and recovery of victims. These differences pose challenges in ensuring justice for DV victims while maintaining military discipline within the institution. The study concludes that harmonizing legal policies between military and civilian courts is necessary to enhance the effectiveness of handling DV cases involving military personnel. This effort aims to achieve a balance between protecting victims and enforcing rules within the military environment. Keywords : domestic violence, military courts, civilian courts